Determinants of Macroeconomic Variables and HDI on Indonesia's GDP Using the ARDL Method - Wine, Wine; Rahajuni, Dijan; Sambodo, Herman; Purwaningtyas, Putri (FORUM EKONOMI: Jurnal Ekonomi, Manajemen dan Akuntansi, 2025)
The successful performance of economic development is calculated by constant price economic growth or real Gross Domestic Product (GDP). Indonesia's GDP value from 1990-2021 tends to increase, but its growth fluctuates. This study aims to analyze the effect of macroeconomic variables including household consumption, foreign investment, domestic investment, economic openness and the Human Development Index (HDI) on Indonesia's GDP in the short and long term 1990-2021. The analysis technique uses Autoregressive Distributed Lag (ARDL). Analysis through the EViews application results: 1). In the short term, the consumption variable has a positive impact on Indonesia's GDP. Foreign investment, on the other hand, has a negative impact. Domestic investment shows a significant positive effect, while economic openness has a significant negative effect on GDP. Additionally, the Human Development Index (HDI) variable demonstrates a significant negative impact on Indonesia's GDP in the short term.; 2). Looking at the long term, only the HDI variable exhibits a significant positive effect on Indonesia's GDP. The implications of increasing GDP and economic growth, leading to higher consumption in society in the short term, necessitate the implementation of policies aimed at improving the wage system and social security. Moreover, attracting foreign investment becomes crucial in sectors where the government and domestic investors cannot operate effectively. For domestic investment, it is essential to deregulate investment arrangements and encourage more proactive investment services to support increased productivity and meet domestic needs. Economic openness can be achieved by boosting exports of finished goods rather than raw materials. Simultaneously, efforts to improve the Human Development Index (HDI) must be evenly distributed both in the short and long term